Meminimalisir Terjadinya Pemalsuan Akta Pejabat Pembuat Akta Tanah (PPAT) dengan Menggunakan Barcode pada Minuta Akta PPAT - Novanto, Brian Shella (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024)DO - 10.24843/AC.2024.v09.i01.p11, 2024)
The aim of this research is to carry out an analysis of the effectiveness of the use of barcodes used in the deeds of Land Deed Making Officials, in order to minimize the occurrence of falsification of deeds made by Land Deed Making Officials and to carry out a review and find out the regulatory procedures related to the use of barcodes. in Government Regulation Number 37 of 1998 concerning Officials Making Land Deeds. The type of research used in this research is empirical legal research. The results of this research are the installation of barcodes on deeds made by Land Deed Making Officials which aims to minimize the occurrence of falsification of deeds by irresponsible individuals and conversely barcodes can also speed up the process of verifying deed files by quickly installing barcodes on deeds. Land Deed Making Officials cannot reducing the existence of those listed in the applicable Legislative Regulations, not only those related to the regulations governing barcodes in Government Regulation Number 37 of 1998 concerning Officials Making Land Deeds. There is still no explicit regulation regarding the use of barcodes in the Deeds of Land Deed Officials, but this has been regulated in Government Regulation Number 82 of 2012 concerning Implementation of Systems and Information and Law Number 11 of 1008 concerning Information and Electronic Transactions.